World energy assessment : overview : 2004 update (New York, NY United Nations Development Programme, Bureau for Development Policy, 2004)
This publication describes energy's fundamental relationship to sustainable development and analyzes how energy can serve as an instrument to reach that goal. Current information on energy production and consumption patterns, technology trends, and i mportant decisions and recommendations made by the Commission on Sustainable Development are included in this publication.--Publisher's description.
Introduction -- Energy at the World Summit for Sustainable Development -- Basic energy facts -- Energy and major global issues -- Energy resources and technological options -- Are sustainable futures possible? -- Policies and actions to promote energy for sustainable development.
"Sales Number: E.04.III.B.6"--P. [2] of cover.
Includes bibliographical references (p. 76-77).
Available both in print and online.
Keywords: Energy development; Power resources; Sustainable development; ENERGY RESOURCES DEVELOPMENT; ENERGY STATISTICS; SUSTAINABLE ENERGY